Understanding the election results in Portugal : A spatial econometrics point of view - Caleiro, António (2018)
The great majority of the theoretical analyses about electoral cycles has considered the national space as the territory of interest when studying the economic consequences of an electoralist behaviour by the central government. This fact, in conjunction to the nature of the data most commonly available, has lead many authors to empirical studies that test the evidence of electoral cycles mostly at a national level. Given that the election results for the main parties, at least in Portugal, clearly reflect some spatial localisation we find rather intriguing to verify that so very few of those empirical studies use spatial econometrics techniques. The main objective of the paper is to detect empirical evidence supporting the existence of a link between voters’ ideology and the 2002 election results obtained by the two main parties in Portugal. The confrontation of the spatial econometric results with the ones obtained ignoring the spatial localisation of the data shows that, in order to better understand the election results, space must be taken into account.